Building a proposed counseling program based on Meckenbaum's theory to improve the cognitive structures of partner selection among unmarried female students (Journal of the College of Basic Education, 2023)
The concept of cognitive structures is widely used in the field of educational psychology in general and cognitive psychology in particular, but it does not imply a single meaning that enjoys general agreement or acceptance.(Al-Zayat: 1996, 416)Cognitive structures consist of a group of general concepts, followed by a group of intermediate concepts, then sub-concepts or sub-concepts, and so on. Each individual has his own knowledge structures. (Atiu, 2013: 240)Mickenbaum explains the cognitive structures as the system of thinking that directs the method and choice of ideas, and he benefits from the executive operator that holds the maps of thinking and determines when to interrupt and when to continue thinking. Human behavior is affected by the different aspects of his activities, which are directed by various formations such as physiological responses, emotional reactions, cognitive aspects, and relationships with others. The inner speech is considered one of these activities and formations. (Al-Shinawi, 1994: 119-123)The current research aims to identify the construction of a counseling program based on Mckenbaum's theory to improve the cognitive structures for partner selection among unmarried female students in the College of Basic Education. After extracting the psychometric characteristics of the scale, it was applied to a sample consisting of (30) divided into two groups, (15) female students for the experimental group and (15) female students for the control group. The researcher used appropriate statistical methods. The results showed that there was good effectiveness, which means that the counseling program was effective It has already contributed to improving the cognitive structures of unmarried female students in the College of Basic Education in the experimental group, and in light of the results of the research, the researcher put forward a number of recommendations and proposals.Keywords: counseling program, Mckenbaum's theory, cognitive structures, partner selection, unmarried female students.